In-between Calvinism and Islam: Ali Bey's Transcultural Translation of the Bible into Turkish in the Time of Confessionalization - Agnieszka Ayşen Kaim (The Biblical Annals, 2023)
Albertus Bobovius/Ali Ufkî Bey was a typical go-between of his time, a learned translator and convert who benefited from his double religious sensitivity. As a consequence, he was able to create a transcultural translation of the Bible in the 17th century. This paper brings context to these aspects of his life. Ali Ufkî Bey created his works on religion during a time of intensive confessionalization, when Istanbul was a hub for many political interests with various religious and cultural options intersecting in the Ottoman capital. The project of translating the Bible to the national languages of Islam was carried out according to the vision of an alliance between Islam and reformed Christian groups, supporting the thesis of Calvino-Turkism, promoted by John Amos Comenius. As oriental scholars were lacking sufficient command of Turkish, they had to commission highly qualified go-betweens. There were two competing plans: Dutch Calvinist and Anglican. Bobovius was a part of the Dutch plan, along with Yahya Bin Ishak, a Jewish dragoman. The strategies of translation chosen by Bobovius were very modern according to the present knowledge of the art of translation, but in his era, there were difficulties in choosing the right language register and the right religious imagery to find proper equivalents. Underestimated by his contemporaries, Bobovius was rehabilitated by today’s linguists, and his “Turkish Bible” is still in use today. The text does not contest the religious identity of the author of this translation of the Bible but presents the hybridity of this figure against the background of the wider historical and confessional context of 17th-century Istanbul. It also provides examples of Bobovius’s translation choices and an initial interpretation of his methodology of timeless transcultural translation, from the perspective of contemporary translation theories. In the light of contemporary transcultural studies, present-day scholarship may treat Ali Ufkî as a transcultural agent and a gifted go-between.